2017
DOI: 10.1002/app.45090
|View full text |Cite
|
Sign up to set email alerts
|

Poly(hydroxybutyrate‐co‐hydroxyvalerate) and bovine serum albumin blend prepared by electrospinning

Abstract: Electrospinning is a method for the preparation of nanosized polymer fibers. Here, electrospinning is used to prepare a blend of a polyester, poly(hydroxybutyrate‐co‐hydroxyvalerate) (PHBV), and a globular protein, bovine serum albumin (BSA). The electrospun blend film is compared with a solution‐cast blend film and with single‐component electrospun films made of PHBV and BSA. In the electrospun blend films, BSA manifests itself as flat ribbons and a fine network formed from fibers less than 50 nm in diameter.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…The enthalpies of fusion of the drug-loaded samples included the small contribution of the shoulder at the lower temperature side of the melting peak, which might be associated with the CPX dehydration, hence even overestimating their crystallinity to some extent. As expected, the melting temperatures and enthalpies decreased with an increase in the 3HV content of the copolymers, which was ascribed to a decrease in crystallinity and crystal perfection [24,34,35]. Additionally, the PHBV-CPX peaks are usually broader and smaller than those of the neat PHBV yarns, which may also be attributed to the formation of crystals with lower perfection and broader size distribution, suggesting an overall deterioration of the crystalline morphology of the PHBV-CPX materials [35,36].…”
Section: Thermal Crystallinity and Molecular Characterizationmentioning
confidence: 72%
“…The enthalpies of fusion of the drug-loaded samples included the small contribution of the shoulder at the lower temperature side of the melting peak, which might be associated with the CPX dehydration, hence even overestimating their crystallinity to some extent. As expected, the melting temperatures and enthalpies decreased with an increase in the 3HV content of the copolymers, which was ascribed to a decrease in crystallinity and crystal perfection [24,34,35]. Additionally, the PHBV-CPX peaks are usually broader and smaller than those of the neat PHBV yarns, which may also be attributed to the formation of crystals with lower perfection and broader size distribution, suggesting an overall deterioration of the crystalline morphology of the PHBV-CPX materials [35,36].…”
Section: Thermal Crystallinity and Molecular Characterizationmentioning
confidence: 72%
“…Second, the electrospinning of BSA solutions in HFIP resulted mostly in ribbons. This is not surprising since many proteins tend to form ribbons rather than bersgelatin, 35 BSA, 18,36 human serum albumin, 16 silk broin. 37 The SEM images of electrospun PLA-BSA blends are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A similar BSA release prole was obtained for electrospun polystyrene-BSA mats prepared by emulsion electrospinning 55 and for the blended poly(hydroxybutyrate-cohydroxyvalerate)-BSA mats. 36 Although preparation of blended PLA-BSA mats was accompanied by the dissolution of BSA in HFIP which can promote the formation of alpha-helices in proteins and peptides and cause protein denaturation, 56,57 we expect the denaturation effect to be relatively low since BSA has a high content of alpha-helices. Previously we demonstrated that HFIPtreated BSA could bind with the anti-BSA antibodies.…”
Section: Bsa Release From the Blended Matsmentioning
confidence: 99%
“…For this to be truly realised, future studies need to consider protein stability and bioactivity in more detail, and use therapeutic biomolecules rather than model proteins. 64,65 With the constantly growing interest in protein therapeutics, it is anticipated that the next decade will bring more insight into the intricacies of electrospinning as a formulation route for biologic APIs. Beyond proteins, it has been shown that cells can also be processed by ES without loss of activity.…”
Section: Electrospinning and Proteinsmentioning
confidence: 99%